A Saturnalia of Bunk : Selections from The Free Lance, 1911-1915 - Mencken, H. L. (Henry Louis), 1880-1956 (Book collections on Project MUSE., 2017)
"H. L. Mencken's reputation as a journalist and cultural critic of the twentieth century has endured well into the twenty-first. His early contributions as a writer, however, are not very well known. He began his journalistic career as early as 1899 and in 1910 cofounded the Baltimore Evening Sun. The next year he initiated a column--The Free Lance--that ran six days a week for four and a half years, until the Sun discontinued it, partially in response to Mencken's controversial defense of Germany during World War One. In this early forum for his renowned wit, Mencken broached many of the issues to which he would return again and again over his career, establishing himself as a fearless iconoclast willing to tackle the most divisive subjects and apply a heady mix of observation, satire, and repartee to clear away what he regarded as the 'saturnalia of bunk' that clouded American thinking. The Free Lance reveals Mencken at his scintillating best as a journalist, polemicist, and satirist. These columns are collected here for the first time, edited and annotated by Mencken expert and critic S.T. Joshi. This extraordinary collection is an invaluable resource for Mencken scholars and fans and provides an entertaining immersion into the early twentieth-century American zeitgeist"--Provided by publisher.